Development of PCR based assays for detection of lethal Holstein haplotype 1, 3 and 4 in Holstein Friesian cattle. (April 2020) - Kumar, Anshuman; Gupta, I.D.; Mohan, Govind; Vineeth, M.R.; Ravi kumar, D.; Jayakumar, S.; Niranjan, S.K.
Abstract: Holstein haplotype (HH) 1, 3 and 4 are lethal mutations, responsible for early embryonic losses in Holstein Friesian (HF) cattle, worldwide. Three PCR based assays – tetra Amplification Refractory Mutation System PCR, PCR primer induced restriction analysis and PCR-restriction fragment length polymorphism techniques for screening of HH1, 3 and 4, respectively were developed and validated. During screening, six among 60 HF bulls were found as carrier for either of three mutations. These PCR assays are highly accurate and reproducible and can be used for screening of the haplotypes in HF cattle. Highlights: PCR assays were developed for detection of Holstein haplotypes-1, 3, 4 associated with embryonic death in cattle. These assays are economical, easier to handle and highly reliable. Screening of these haplotypes resulted in presence of carriers in Indian Holstein cattle with 10 percent of frequencies. The assays can also be used for cross-validation of the results obtained from DNA Chip based screening.